2011
DOI: 10.1097/tp.0b013e3182106069
|View full text |Cite
|
Sign up to set email alerts
|

Early Reexploration for Suspected Thrombosis After Pancreas Transplantation

Abstract: Reexploration for suspected graft thrombosis after pancreas transplantation resulted in a negative laparotomy rate of 43%, but permitted graft salvage in 45% of compromised grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 36 publications
0
47
0
Order By: Relevance
“…It is likely that only those pancreata with mild damage were implanted, introducing bias into the analysis. Furthermore, the majority of injured organs had a shortened portal vein (defined as less than 10 mm length), and some surgeons believe that this reduces the rate of venous thrombosis (20,21). In any case, the use of a portal vein extension graft does not appear to increase the rate of graft loss (22).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that only those pancreata with mild damage were implanted, introducing bias into the analysis. Furthermore, the majority of injured organs had a shortened portal vein (defined as less than 10 mm length), and some surgeons believe that this reduces the rate of venous thrombosis (20,21). In any case, the use of a portal vein extension graft does not appear to increase the rate of graft loss (22).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no consensus on the classification or reporting of PAT, it is generally categorized as either complete or partial 16. Complete occlusion usually results in graft loss, unless thrombectomy or thrombolysis are undertaken soon after onset 17, 18, 19, 20. Conversely, there is some evidence to suggest a higher likelihood of pancreas allograft salvage with anticoagulation alone after partial thrombosis, although other interventions are occasionally required 21, 22.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Fridell et al [5] reported 343 pancreas transplants, in which early urgent re-exploration for suspected graft pancreas thrombosis was indicated based on the presence of an unexplained hyperglycemia or the failure to achieve euglycemia 1 week after grafting. This approach resulted in 35 early surgical re-explorations with the graft being compromised in 20 (57 %) cases, 10 of which involved venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of randomization and a control group treated with anticoagulation prevents to assess in what number of these patients, particularly those with thrombus 30-60 % in length, anticoagulation alone would have been effective. The current literature dealing with the available salvage strategies is retrospective without comparing the different treatment options [4][5][6][7][8][9][10][11][12]. The low incidence of PVGT makes it difficult to compare the treatment options in a prospective randomized study in a single institution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation